2017
DOI: 10.3329/seajph.v6i2.31830
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Problems in Bangladesh: Issues and challenges

Abstract: In South-East Asia the main public health issues are infectious diseases and communicable diseases. Public health has improved markedly in Bangladesh over the past three decades. Nevertheless, Bangladesh faces major health challenges. A scoping study was performed according to York methodology. The study was aimed to find out the major public health issues and challenges in Bangladesh. Bangladesh has one of the worst burdens of childhood malnutrition in the world. Communicable diseases are a major cause of dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 3 publications
0
25
0
Order By: Relevance
“…Unsafe food remains a major threat to public health each year; citizens suffer from the acute effects of food contaminated by microbial pathogens, chemical substances and toxins. There is a need to minimize the consumer's exposure to unhygienic, contaminated and adulterated food and drinks through strict laws to control marketing of such products [21]. One such factor is violence against women.…”
Section: Health Issues and Challenges In Bangladeshmentioning
confidence: 99%
See 3 more Smart Citations
“…Unsafe food remains a major threat to public health each year; citizens suffer from the acute effects of food contaminated by microbial pathogens, chemical substances and toxins. There is a need to minimize the consumer's exposure to unhygienic, contaminated and adulterated food and drinks through strict laws to control marketing of such products [21]. One such factor is violence against women.…”
Section: Health Issues and Challenges In Bangladeshmentioning
confidence: 99%
“…This is a widespread social problem that causes mental stress, physical suffering and even death, and is believed to be grossly underreported. One study reveals that in Bangladesh about 52% of men in both urban and rural sites reported ever physically assaulting female intimate partners [21].…”
Section: Health Issues and Challenges In Bangladeshmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4] TB and malnutrition are major public health problems in Bangladesh where Bangladesh still ranks among the top ten countries in the world with the highest TB burden. 5 Here in Bangladesh, around 186 people die of TB every day and around 68 000 per year. 6 In 22 high tuberculosis-burden countries Bangladesh is one of them.…”
Section: Introductionmentioning
confidence: 99%